(untitled) (IYUNIM: Multidisciplinary Studies in Israeli and Modern Jewish Society, 2026)
In this article. I examine the connection between Rabbi Nachman of Breslov’s parable, "The Rooster Prince," and Shmuel Yosef Agnon’s A Simple Story. I claim that the Hassidic story is a link between the traditional Hebrew story and modern Hebrew literature. Although this Hassidic tale was not published until 1935, it was apparently transmitted orally among Breslov Hasidim, and it is likely that Agnon, who maintained close connections with this community, was familiar with this folktale. In this article, I recognize structural parallels and central themes: the son of a respectable family who goes mad, conventional physicians whose treatments fail, and one extraordinary carer who succeeds, through profound empathy and attentiveness. The rooster motif is central to both stories, as are references to disrobement, eating disorders, and parental grief. I compare the treatment procedures adopted by Dr. Langsam and the Wise Man, whose methods are based on empathy, listening, and the gradual establishment of social capabilities. I also engage with the meta-poetic references within both stories ("the moral of the story is clear to those who understand"; "our simple story"), which invite us to ponder the role of the story itself as a therapeutic space. Both authors identify the narrator with the character of the carer and perceive the story itself as a tool of mental restoration. My conclusion is that Agnon developed the Hassidic story into a complex examination of society and psyche, whilst maintaining the perception of literature as a transformative-therapeutic space.